A geohydrological situation analysis for the construction of a groundwater management plan for the Sasolburg industrial and mining area - Cowley, Jennifer Anne (University of the Free State, 1999)
English: The Department of Water Affairs in South Africa has recently moved towards the management of regions on a catchment and subcatchment scale. The Taaibos and Leeu Spruit catchments were identified as catchments where groundwater research was needed. The final objective of this work would be the implementation of a Catchment Management Plan These catchments house several influences on groundwater quality. These include the urban area of greater Sasolburg, several chemical industries (petrochemical, fertilizers, plastics ete), mining activities, power stations and agriculture. A groundwater situation analysis was therefore undertaken to highlight all relevant groundwater components. To achieve this, the study included a literature study, the creation of a database, fieldwork including sampling of 101 sites in the catchment for inorganic analysis, sampling of 10 sites for toxicity testing to indicate true toxicity of the water, aerial geophysics over a portion of the catchment and resistivity soundings at points surrounding the industries. Based on information gathered by this work it was possible to identify the principal aquifers in the area and classify them according to methods set out by Parsons (1995). The chief controls on groundwater movement and pollution sources on each site were identified. It was found that a dolerite sill of variable depth and thickness was the main control of groundwater movement underlying the industrial areas. The collected data and sampling highlighted the most important pollution sources. Use of toxicity testing showed the potential of these tests in indicating the true toxicity of samples. These results with, simplified numerical modelling in the area gave an indication of pollution migration and areas of concern. The area was subdivided into groundwater management areas based on the activities in each area. Three zones were defined representing the industrial and mining areas, a buffer zone and the areas to be protected respectively. In each zone different quality guidelines were proposed. A Threat Action Guide spreadsheet was developed to identify and prioritize areas of concern. It uses water quality data for different parameters, the aquifer classification, the water quality guideline for the zone and the distance to the nearest area of concern as inputs. A threat index is thereby calculated using various empirical equations and this index then suggests different generalized management options to be followed. The situation analysis has provided an overview of this heterogeneous area and put a basic framework in place on which the eventual Groundwater Management Plan will be based.

Afrikaans: Die Departement van Waterwese en Bosbou het onlangs begin om die bestuur van grondwater op 'n opvangsgebied en sub-opvangsgebied sisteem te baseer in plaas van streke. Die Taaibosspruit en Leeuspruit opvangsgebiede was geïdentifiseer as opvangsgebiede waar grondwaternavorsing nodig is. Die uiteinde van sulke werk sallei tot die opstel van 'n grondwaterbestuursplan. Daar is verskeie instansies wat 'n invloed op die grondwater kwaliteit in hierdie opvangsgebiede kan hê. Van hierdie instansies sluit die verskeie chemiese industrieë (petrochemies, kunsmis, plastiek, ens.), myne, kragstasies en landbou in. 'n Grondwatersituasie-analise is onderneem om al die relevante grondwater komponente aan te spreek. Die studie het die volgende behels: (a) literatuurstudie; (b)opstel van 'n databasis; (c)veldwerk wat die neem van 101 grondwatermonsters vir anorganiese analise en 10 monsters vir toksisiteits toetse; asook grond- en lug geofisika ingesluit het. Gebaseer op die inligting wat ingesamel was, is die hoof akwifere in die area geïdentifiseer en geklassifiseer volgens Parson (1995) se metode. Die hoof kontroles oor grondwaterbeweging en besoedelingsbronne was geïdentifiseer in al die areas. Daar is gevind dat 'n dolerietplaat van veranderlike diepte en dikte die hoofkontrole oor grondwaterbeweging in die industriële gebied is. Die ingesamelde data en monsterneming het die belangrikste besoedelingsbronne geïdentifiseer. Toksisiteitstoetse het die potensiaal van hierdie tipe toetse uitgewys om die ware toksisiteit van monsters te weerspieël. Hierdie resultate tesame met vereenvoudigde numeriese modellering, het 'n indikasie van besoedelingsmigrasie en areas van kommer gegee. Die area is in grondwaterbestuursareas ingedeel op grond van die verskillende aktiwiteite. Drie sones is gedefinieër wat die industriële en myn areas, 'n buffersone en areas wat beskerm moet word insluit. Vir elke sone was daar 'n verskillende waterkwaliteitriglyn voorgestel. 'n " Threat Action Guide" spreivel was ontwikkelom die areas van kommer uit te wys en te prioritiseer. Hierdie spreivel gebruik waterkwaliteitdata vir verskillende parameters, die akwifeer klassifikasie, die waterkwaliteitriglyn vir 'n sone en die afstand na die naaste area van kommer, as insette. 'n "Threat" indeks word ook bepaal deur gebruik te maak van empiriese vergelykings en hierdie indeks gee dan moontlike bestuursopsies wat uitgevoer kan word. Die situasie analise het 'n oorsig van 'n heterogene area gegee en het 'n basiese raamwerk daargestel vir die opstel van die uiteindelike grondwaterbestuursplan.
Keywords: Hydrogeology -- South Africa -- Sasolburg; Groundwater -- Quality; Water resources development -- South Africa -- Sasolburg; Dissertation (M.Sc. (Geohydrology))--University of the Free State, 1999